Offshore wind farm wake recovery: Airborne measurements and its representation in engineering models. Issue 5 (18th February 2020) - Cañadillas, Beatriz; Foreman, Richard; Barth, Volker; Siedersleben, Simon; Lampert, Astrid; Platis, Andreas; Djath, Bughsin; Schulz‐Stellenfleth, Johannes; Bange, Jens; Emeis, Stefan; Neumann, Thomas
Abstract: We present an analysis of wind measurements from a series of airborne campaigns conducted to sample the wakes from two North Sea wind farm clusters, with the aim of determining the dependence of the downstream wind speed recovery on the atmospheric stability. The consequences of the stability dependence of wake length on the expected annual energy yield of wind farms in the North Sea are assessed by an engineering model. Wakes are found to extend for significantly longer downstream distances (>50 km) in stable conditions than in neutral and unstable conditions ( <  15 km). The parameters of one common engineering model are modified to reproduce the observed wake decay at downstream distances >  30 km. More significant effects on the energy yield are expected for wind farms separated by distances <  30 km, which is generally the case in the North Sea, but additional data would be required to validate the suggested parameter modifications within the engineering model. A case study is accordingly performed to show reductions in the farm efficiency downstream of a wind farm. These results emphasize not only the importance of understanding the impact of atmospheric stability on offshore wind farms but also the need to update the representation of wakes in current industry models to properly include wake‐induced energy losses, especially in large offshore clusters.